Delayed age of marriage for working women (Journal of the College of Basic Education, 2022)
Our research, marked (delayed age of marriage for working women), is a field study in some governmental departments of the state, to know the most important social and economic reasons that call for delaying the age of marriage for working women, and the most important positive and negative consequences of their work outside the home.